IPRATROPIUM ATTENUATES INSULIN INDUCED TRACHEAL SMOOTH MUSCLE CONTRACTION OF GUINEA PIG IN VITRO: Ipratropium - Sharif, Mahjabeen; Khan, Bushra Tayyaba; Bakhtiar, Salman; Sharif, Mubashir (Pakistan Armed Forces Medical Journal, 2014)
Objective: To evaluate the magnitude of insulin induced tracheal smooth muscle contraction of guinea pigs and exploration of protective effects of ipratropium against insulin induced increased airway reactivity of guinea pigs in vitro.Study Design: Laboratory based randomized control trials.Place and Duration of Study: Pharmacology department and Centre for Research in Experimental and Applied Medicine (CREAM) Army Medical College, Rawalpindi from December 2011 to July 2012.Material and Methods: Effects of increasing concentrations of histamine (10-8- 10-3 M ), insulin (10-8- 10-3 M) and insulin pretreated with ipratropium (10-6 M) , were studied on isolated tracheal tissue of guinea pig in vitro by constructing cumulative concentration response curves. The tracheal smooth muscle contractions were recorded with transducer on four channel oscillograph.Results: Histamine and insulin produced a concentration dependent reversible contraction of isolated tracheal muscle of guinea pig. The mean ± SEM of maximum amplitudes of contraction with histamine, insulin and insulin pretreated with ipratropium were 92.5 ± 1.20 mm, 35 ± 1.13 mm and 27.8± 1.27 mm respectively. Ipratropium shifted the concentration response curve of insulin to the right and downwards.Conclusions: Ipratropium significantly inhibited the contractile response of insulin on isolated tracheal muscle of guinea pig, so pretreatment of inhaled insulin with ipratropium may have clinical implication in amelioration of its potential respiratory adverse effects such as bronchoconstriction.